To make Politics a science: Epistemological Approaches - Begnini, Pablo (Universidad Hemisferios, 2024)
Nowadays, empirical knowledge - based on observation and verification of facts - is considered the highest criterion of validation in science. This has led to the overshadowing of other types of knowledge that are not based on empirical evidence, considering them as speculative or vulgar. This dogmatic attitude has radically modified the research activity, generating distrust in disciplines that do not follow the scientific method, particularly harming the social science. Given these limitations, this work advocates the need to approach knowledge from a broader and more holistic perspective, which favors the approach of the findings of the social science to the construction of a more assertive science. In this sense, we will comment on some of the modern conceptions of the theory of knowledge, trying to guide the reader towards the scientistic perspective and then explain how it has gradually lost credibility in epistemological spheres. In the background and based on the thinking of authors such as the philosopher Karl Popper or the historian Thomas Khun, we will seek to notice how these positions are always inconclusive or reductionist in their desire to understand reality. Finally, we will propose the Aristotelian theory of causality as an epistemological framework for Political Science, to avoid the reduction of knowledge to pre-established concepts and thus enrich human horizons.